Transformasi Benih: Optimalisasi Peran Penangkar benih untuk Pembangunan Nagari Berkelanjutan di Sumatera Barat - Masruri, Masruri; Hadiguna, Rika Ampuh; Suliansyah, Irfan; Henmaidi, Henmaidi (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
In the realm of agricultural development, the governance of seed production plays a crucial role in ensuring food security and sustainable rural development. This study delves into the characteristics and challenges encountered by seed breeders in West Sumatra, Indonesia, as they endeavor to improve seed governance for village development. Through a qualitative research approach, insights were gleaned from 25 seed-breeding farmer groups, shedding light on the intricate dynamics of seed production at the grassroots level. The backdrop of this research is framed against the backdrop of global concerns regarding food security and the pivotal role played by local communities in addressing these challenges. West Sumatra, with its rich agricultural heritage and vibrant farming communities, serves as an ideal setting to explore the complexities of seed governance in the context of village development. The findings of this study illuminate the nuanced challenges faced by seed breeders, ranging from financial constraints to resource limitations and pricing pressures. Moreover, it underscores the importance of collaborative efforts involving companies, farmers, and government agencies in devising sustainable solutions to enhance seed governance. By addressing these challenges, not only can the resilience of local farming communities be strengthened, but it also contributes to broader goals of sustainable rural development and food security. This research serves as a timely contribution to the discourse on agricultural governance and underscores the need for concerted efforts at the stakeholder level to achieve tangible progress in village development.